Civil compensation and loss allocation in authorised push payment fraud: Moving beyond criminalisation in instant payment systems—a comparative study of Jordan and the UK - Samawi, Reem; Abu Rukba, Rami; Hmaidan, Ruba; Aldabbas, Amani; Albadawi, Ahmad; Sweilmieen, Baker (Research Journal in Advanced Humanities, 2026)
The rapid expansion of instant payment systems has transformed retail finance by enabling real-time, irrevocable transfers, while exposing users and institutions to heightened financial crime risks. A key threat is authorised push payment (APP) fraud, where victims are deceived into authorising transfers to fraudsters. This article argues that financial crime in instant payment systems represents a structural risk that cannot be addressed through criminalisation and anti-money laundering compliance alone. Using a comparative legal and regulatory methodology, it examines Jordan’s CliQ system and the United Kingdom’s Faster Payments framework to assess responses to APP fraud and related money laundering risks.The analysis shows that Jordan’s framework prioritises system integrity, prevention, and criminal enforcement, but lacks mechanisms for compensating victims of authorised payment fraud, effectively externalising losses onto individuals. By contrast, the United Kingdom has shifted toward systemic accountability through a mandatory reimbursement regime, redistributing losses across payment service providers rather than leaving them with consumers. This shift reflects recognition of regulatory failure in traditional loss allocation within real-time payment systems.Situating APP fraud within debates on loss allocation, victim protection, and institutional responsibility, the article contributes to scholarship on financial crime governance in digital payments. It proposes a calibrated reform pathway for Jordan, advocating a limited, conditional reimbursement framework that enhances consumer protection without undermining payment finality, criminal enforcement, or anti-money laundering objectives, offering policy-relevant insights for jurisdictions implementing instant payments.